2019
DOI: 10.31234/osf.io/nkcr3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Limited evidence of hierarchical encoding in the cheerleader effect

Abstract: “The cheerleader effect” refers to the increase in attractiveness that an individual face experiences when seen in a group of other faces. It has been proposed that the cheerleader effect occurs because (a) the visual system rapidly summarises a group of faces into an ensemble representation, (b) which is hypothesised to be highly attractive because of its average facial characteristics, and (c) observers remember individual faces to be more alike the ensemble representation than they were, due to hierarchical… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 64 publications
(163 reference statements)
2
5
0
Order By: Relevance
“…By replicating Walker and Vul’s work, the results generated from Study Ia, Ib, and Ic demonstrated that individuals give higher attractiveness ratings when targets are in group member condition (GMR) in comparison to the individual rating condition (IR). Such a result confirmed the cheerleader effect [ 11 ] and was consistent with very recent studies [ 14 , 15 , 16 , 17 , 24 ], therefore extending this finding to a collectivistic culture with a stronger effect size compared to previous studies [ 18 ]. According to the explanations proposed by Walker and Vul [ 11 ], when rating attractiveness: (1) people’s visual system would automatically compute ensemble representations of faces presented in a group; (2) making the individual members of the group biased toward this ensemble average; and (3) average faces were more attractive.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…By replicating Walker and Vul’s work, the results generated from Study Ia, Ib, and Ic demonstrated that individuals give higher attractiveness ratings when targets are in group member condition (GMR) in comparison to the individual rating condition (IR). Such a result confirmed the cheerleader effect [ 11 ] and was consistent with very recent studies [ 14 , 15 , 16 , 17 , 24 ], therefore extending this finding to a collectivistic culture with a stronger effect size compared to previous studies [ 18 ]. According to the explanations proposed by Walker and Vul [ 11 ], when rating attractiveness: (1) people’s visual system would automatically compute ensemble representations of faces presented in a group; (2) making the individual members of the group biased toward this ensemble average; and (3) average faces were more attractive.…”
Section: Discussionsupporting
confidence: 92%
“…Walker and Vul found that people seem more attractive in a group context than in isolation, and such a phenomenon has been coined as the cheerleader effect [ 11 ]. Subsequent studies have been focused on exploring the mechanism behind the cheerleader effect, and to check the generalization of such an effect [ 15 , 16 , 17 , 18 ]. Both attractiveness effects, either the GA-effect or the cheerleader effect, seem to suggest that people in a group context enjoy higher attractiveness rating, irrespective of being rated alone or by comparison to other members within the group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…What causes the social positive effect remains unclear. There is debate on the mechanisms underlying the cheerleader effect, which is observed even though it is incompatible with hierarchical encoding ( Carragher et al, 2019 ). This offers limited evidence for the role of hierarchical encoding in the cheerleader effect ( Luo and Zhou, 2018 ).…”
Section: Discussionmentioning
confidence: 99%